Forensic Evaluation of Suicide - Mitjie Batsebha Sariwating (Jurnal Ilmu Multidisiplin, 2026)
Suicide is one of the causes of unnatural death that has complex medical, psychological, and legal implications. Forensic evaluation of suicide cases often faces challenges due to overlapping pathological findings with accident and homicide cases, especially in cases of hanging and complex suicide. This study aims to systematically analyze forensic evaluation approaches in suicide cases through the integration of conventional autopsy, Post-Mortem Computed Tomography (PMCT), psychological autopsy, toxicology examination, and other contextual analyses. This study uses the Systematic Literature Review (SLR) method with reference to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of 25 articles published between 1992 and 2025 that met the inclusion criteria were analyzed qualitatively. Data were extracted and synthesized to identify research methods, key findings, and the contributions of each approach to forensic suicide evaluation. The results of the study show that conventional autopsy is still the primary method for determining the cause of death, but it has limitations when used alone. The integration of PMCT has been shown to improve the objective detection of neck injuries and internal findings. Psychological autopsy plays an important role in uncovering the psychological and social factors of the victim, especially in ambiguous deaths. Toxicological examination provides crucial information regarding the influence of psychoactive substances on the victim's behavior, while forensic linguistic analysis helps authenticate wills and understand the motives for suicide. In complex suicide cases, a multidisciplinary approach is an absolute necessity.